The Classic-quantum and Single-multiparticle Viewpoints: Water Drops Kinematic Analysis - Daniele De Wrachien; Giulio Lorenzini (Novel Perspectives of Engineering Research Vol. 3, 2021)
The difficulty of a particle traversing a gaseous mean is one of the most challenging modelling problems in science. This applies to a water droplet travelling from the nozzle to the ground in sprinkler irrigation. The challenge primarily refers to the intense difficulty in writing and solving the system of governing equations for such a complicated process, where many non-linearities occur when describing the relationships and dependences between one influential parameter and another. When a multi-droplet system is considered instead of just a single droplet, the problem becomes even more complicated because, in addition to inter-parameter dependencies, an inter-droplet reciprocal affection is observed, owing to electrical interactions between the hydrogen and oxygen atoms of the different water molecules. A quantum approach has recently been proposed as an alternative to traditional classic approaches to analyse water droplet dynamics in sprinkler irrigation, but the entire classic-quantum and single-droplet versus multi-droplet alternatives need to be discussed and pinpointed, which is one of the main goals of the current paper, which focuses on the theoretical part of the issue, thus highlighting the new perspectives of a deeper comprehension in the spray flow related phenomena.